SIMULATION OF CO2 FLOW MODEL IN DEPLETED GAS RESERVOIR ON CARBON CAPTURE AND STORAGE (CCS) PROCESS - Hery Sudibio, Made
One of the solution to reduce Green House Gas (GHG) emissions, particularly carbon dioxide (CO2) is applying Carbon Capture and Storage (CCS). CCS is process of separation and capture of CO2 from industrial process emissions and then transported and stored it permanently. Depleted gas reservoir is a promising location for the storage of CO2 in geological formation since natural gas reservoir has been proven to retain gas keep in reservoir for a very long time. Additionally reservoir characteristics are well known and existing infrastructure can be reused on the possibility of the injection process. Indonesia has great potential to apply CCS processes in depleted gas reservoir. So understanding the mechanism of fluid flow in depleted gas reservoir is critically important. Several mechanism of fluid flow that occurs on injection of CO2 in depleted gas reservoir is the advection (movement of fluid due to pressure gradient), buoyancy (movement of fluid due to density differences) that can be discribed by Darcy’s Law and diffusion process. This study aims to understand and build a model that can describe the mechanism of CO2 storage and transport phenomena, determine parameters that influence the mechanism of CO2 of the injection process, determine energy requirements and emissions generated, determine the ratio between emissions generated to the injected CO2 and estimate the storage capacity and minimum injection pressure required in the process of CO2 injection in depleted gas reservoir for a certain period of time. The result showed that the mechanism is affacted by CO2 injection pressure and CO2 injection rate. For the injection pressure 4.8 MPa, time to reach equilibrium pressure is 250 days, the fraction of CO2 is 0.755, and for the injection pressure 8.3 MPa, time to reach equilibrium pressure is 330 days, the fraction of CO2 is 0.717. While for injection rate of 10 MMSCFD, CO2 fraction is 0.717, and for injection rate 50 MMSCFD, CO2 fraction is 0.965. Power requirements for injection pressure variation at 4.8 MPa is 9097 kW, pressure injection 8.3 MPa is 10576 kW and for injection rate variations the power requirement at 10 MMSCFD is 2115 kW, for 50 MMSCFD is 10576 kW. The ratio between the CO2 emissions generated to the injected CO2 has increased for variaton of injection pressure, at 4.8 MPa the ratio is 0.048, at 8.3 MPa the ratio is 0.056, while the ratio for iv variation of injection rate has the same value (injection rate had no effect on the ratio CO2 emissions-injection). For injection time about 20 years at 10 MMSCFD injection rate, the amount of CO2 that has been stored is 3.8x106 tonnes and the minimum injection pressure is 630 psia, while at 50 MMSCFD, the amount of CO2 that has been stored is 1.92x107 tonnes and the minimum injection pressure is 1110 psia.